Africa's Thorny Horn Searching for a New Balance in the Age of pandemic - Carbone, Giovanni (ISPI Publications, 2020)
In the context of the disruption caused by the Covid-19 pandemic, the Horn of Africa remains one of the most dynamic and intriguing regions on the African continent. The political processes currently under way - including the recent conflict in Ethiopia's Tigray region - have deep implications that reflect on the domestic equilibria within the area's core states - Ethiopia itself, but also Eritrea, Somalia and Djibouti - as well as on the relations among them. The nature and extent of involvement by external, non-African players is bound to be affected too. How is the Horn of Africa changing, following the leadership transition in Ethiopia? What are the main political and security prospects for the region and for the states belonging to it? And how will ongoing dynamics impact on European political strategies?